2009
DOI: 10.1016/j.icarus.2008.12.018
|View full text |Cite
|
Sign up to set email alerts
|

OMEGA/Mars Express: South Pole Region, water vapor daily variability

Abstract: Polar regions on Mars are the most suitable places to observe water vapor daily variability because in any observation crossing the Pole we can observe very different local time and because the poles are considered to be the main permanent and seasonal water reservoir of the planet.We report on a daily variability of water vapor in the south pole region (SPR), observed by OMEGA/Mars Express during the south spring-summer period (Ls∼250 • -270 • ) outside the CO 2 ice cap, that has never been observed before by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…Formisano et al (2001) studied the water vapor diurnal cycle in southern mid-latitudes at L s = 290-340°with the Mariner 9 data and observed diurnal changes in column abundances of up to 10 pr-lm, which they attributed to exchange with the regolith. Melchiorri et al (2009) observed diurnal variability of several precipitable micrometers near the South Pole during summer and also attributed it to the exchange with regolith. These examples demonstrate the magnitude of the possible diurnal effect.…”
Section: Comparison With Other Datasetsmentioning
confidence: 82%
“…Formisano et al (2001) studied the water vapor diurnal cycle in southern mid-latitudes at L s = 290-340°with the Mariner 9 data and observed diurnal changes in column abundances of up to 10 pr-lm, which they attributed to exchange with the regolith. Melchiorri et al (2009) observed diurnal variability of several precipitable micrometers near the South Pole during summer and also attributed it to the exchange with regolith. These examples demonstrate the magnitude of the possible diurnal effect.…”
Section: Comparison With Other Datasetsmentioning
confidence: 82%
“…Using the OMEGA data Melchiorri et al (2009) have observed a increase in water vapor from 5:00 (2 pr. lm) to 16:00 (10 pr.…”
Section: Local Time Variationsmentioning
confidence: 99%
“…The thermal infrared range was used by the IRIS instrument aboard Mariner 9 (Conrath et al 1973), then by TES aboard Mars Global Surveyor (Smith 2002(Smith , 2004) and more recently by PFS aboard Mars Express ). In the reflected spectrum, both the MAWD experiment aboard Viking and SPICAM aboard Mars Express used the 1.38 μm H 2 O band (Farmer et al 1977;Jakosky & Haberle 1992;Fedorova et al 2004Fedorova et al , 2007 while OMEGA aboard Mars Express (Encrenaz et al 2005Melchiorri et al 2007Melchiorri et al , 2009Maltagliati et al 2007Maltagliati et al , 2008 and CRISM aboard Mars Reconnaissance Orbiter ) used the 2.6 μm H 2 O band, still in the reflected solar spectrum. All these analyses however have a common limitation, which is the lack of simultaneous mapping of the planet.…”
Section: Introductionmentioning
confidence: 99%
“…There is actually an exception, when the orbital sequence crosses the polar region. In this case, morning and evening data can be acquired in a single orbit; however, this method is limited to the study of high latitude regions (Melchiorri et al 2009). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation